DEVELOPMENT OF SOFTWARE TO EVALUATE ROOF FALL RISK IN BORD AND PILLAR METHOD - DEPILLARING PHASE - Nimaje, Devidas S; Sai, Shiva (GeoScience Engineering, 2015)
Roof fall is one of the major problems of the bord and pillar coal mines during the depillaring phase. Roof fall not only causes considerable damage to the mining equipment but also to the miners. To keep in view, development of software is essential for the calculation of roof fall risk to reduce the accidents to a certain extent. In this paper, the software has been developed and tested on seam-2, the main panel of RK-5 underground coal mine, Singareni Collieries Company Limited, India and corresponding roof fall risk was calculated. The best combination of the parameters causing roof fall risk was evaluated to reduce the risk.